The Influence of Animation Media on the Short Story Writing Ability of Class X Students of MAL UINSU Medan - Elfina Wety; Faridah Faridah (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to explore the influence of animation media on the ability to write short stories of class X students. In the quantitative method, the researcher used Quasi Experimental research with the type of Nonequivalent Control Group Design. The researcher used two groups consisting of an experimental group that was given treatment using a problem-based learning model and a control group that was not given treatment/conventional. The results of this study were obtained from the results of the pretest and posttest. The purpose of the pretest is to determine the learning outcomes of students before learning using animation media. While the purpose of the posttest is to determine the learning outcomes of students after learning using animation media. Implementation and application of the results of the pretest posttest in the experimental and control classes. This study shows that the use of animation media has a significant influence on improving the ability to write short stories in class X students. Based on the results of data analysis, it was found that students who learned using animation media showed a higher increase in learning outcomes compared to students who used conventional methods. This is proven through valid data normality and homogeneity tests, as well as hypothesis tests (t-tests) which showed significant differences between the results of the pretest and posttest, especially in the experimental group.